Pengaruh Inventory Intensity, Capital Intensity, Likuiditas Terhadap Agresivitas Pajak (Studi pada Perusahaan Subsektor Pertambangan Batu Bara pada Bursa Efek Indonesia Tahun 2015-2019) - Lapida, Lapida; Lady Silvera, Dica (Fakultas Ekonomi, Universitas Ekasakti, 2023)
The aim of the research is to prove and analyze individually or collectively the influence of inventory intensity, capital intensity, and liquidity on tax aggressiveness. The sample in this research is a coal mining company on the Indonesia Stock Exchange. The data used is from 2015 to 2019. The data analysis method to prove the truth of the hypothesis is multiple regression t-statistical testing and F-statistical testing. Hypothesis testing using the SPSS program. Based on the results of the hypothesis test, it was found that capital intensity and liquidity had a significant influence on tax aggressiveness in coal mining sub-sector companies on the Indonesia Stock Exchange, while inventory intensity had no significant effect on tax aggressiveness in coal sub-sector companies on the Indonesia Stock Exchange. Apart from that, inventory intensity, capital intensity, and liquidity all have a significant influence on tax aggressiveness in coal mining sub-sector companies on the Indonesia Stock Exchange.